Manipulating proteinprotein interactions through high pressure and enzymatic combined treatments to tailor food properties - Queirós, Rui Pedro Figueiredo Neto (2020)
The demand for proteins is rising and alternatives to animal-based proteins are necessary, either for nutritional or environmental reasons. Plant-based proteins appear as an alternative, however, their techno-functional properties need improvement. High-pressure processing (HPP) is a non-thermal technology that allows modifying proteins’ structure hence allowing to change several of their properties. Enzymes, such as microbial transglutaminase (MTG), can also modify the techno-functional properties of proteins, however, many globular proteins show low susceptibility to the action of this enzyme. HPP, being able to change protein conformation, may be a useful tool to increase the accessibility of proteins to the action of MTG. Nevertheless, HPP conditions need to be carefully optimized to avoid the expected decrease in enzymatic activity when subjected to pressure. Pressure inactivation of MTG under different HPP conditions (200 – 600 MPa; 20 – 40 °C; 10 – 30 min) was evaluated at different pH values. At least 20 % of MTG was inactivated when low pressures (< 300 MPa) were used at pH 4 and 5, whereas a higher pressure (above 400 MPa) was needed to obtain a similar inactivation at pH 6 or 7. MTG pressure-inactivation followed first-order kinetics under all tested conditions. Inactivation rate constants decreased with increasing pressure at constant temperature and pH 4, with a positive activation volume, while the opposite was verified for the other pH values. Both activation energy and volume were dependent on pH. Overall, MTG can be considered relatively resistant to pressure, particularly near its optimal pH. The influence of HPP (200 – 600 MPa; 5 – 15 min) was also evaluated, applied individually or in combination with MTG (up to 30 U·g-1), on selected properties of pea (PPI) and soy (SPI) protein isolates with concentrations between 1 and 9 % (w/v). For a protein concentration of 1 % (w/v), HPP increased the protein solubility of both isolates when applied individually. This effect was more pronounced for SPI, particularly at pH 7 and 8. Similarly, the protein surface hydrophobicity also increased with HPP for proteins from both sources, increasing, in general, with increasing pressure and holding time. On the contrary, the content of free sulfhydryl groups decreased with HPP for proteins from both sources. The effects of HPP on the emulsifying properties of the protein isolates, considering both the whole and soluble protein fractions, were dependent on pH and HPP conditions (pressure, holding time). HPP appeared to have minimal effects on the surface tension of both proteins and the general absence of negative effects on emulsifying activity results from HPP-induced protein aggregation effects. On the other hand, MTG individual treatments had no significant effects on the studied properties. For the other protein concentrations studied, HPP increased the solubility of proteins when there were at low initial concentrations, decreasing it when they were in the higher concentration range analysed. Regardless of the concentration, HPP decreased the content of free sulfhydryl groups for pea proteins, however, had the contrary effect on soy proteins. Comparably to the solubility, the surface hydrophobicity increased in low protein concentrations and the contrary was verified in high protein concentrations. MTG decreased solubility and increased the content of free sulfhydryl groups of both proteins. The enzyme decreased the surface hydrophobicity of soy proteins and of the pea proteins, but only when these were within the higher concentration range analysed. When combined, HPP and MTG appear to have antagonistic effects on the solubility and content of free sulfhydryl groups and synergistic effects on viscosity. The obtained results indicate that simultaneous HPP and MTG treatments can be used to modify the proteins’ structure and consequently tailor their techno-functional properties.